The seasonal reproduction number of dengue fever impacts of climate on transmission - Polwiang,Sittisede (PeerJ Preprints, 2016)
Background: The dengue fever is a mosquito-borne viral disease and a regular epidemic in Thailand. The peak of the dengue epidemic period is around June to August during the rainy season. It is believed that the climate is an important factor for dengue transmission.Method: A mathematical model for vector-host infectious disease was used to calculate the impacts of climate to the transmission of dengue virus. In this study, the data of climate and dengue fever cases were derived from Chiang Mai during 2008-2015, Thailand. The value of seasonal reproduction number was calculated to evaluate the potential, severity and persistence of dengue infection.Results: The mosquito population was increasing exponentially from the start of the rainy season in early May and reached its the peak in late June. The simulations suggest that the greatest potential for the dengue transmission occurs when the temperature is 28.9ºC. The seasonal reproduction numbers were larger than one from late March to end of August and reaching the peak in June. The highest incidences occurred in August due to the delay of transmission humans-mosquito-humans. Increasing mean temperature by 1.2ºC, the number of incidences increases 43.7%. However, a very high or very low temperature reduces the number of infection.Discussion and Conclusion: The results show that the dengue infection depends on the seasonal variation of the climate. The rainfall provides places for the mosquitoes to lay eggs and develop to adult stage. The temperature plays an important role in the life cycle and behavior of the mosquitoes. A very high or very low temperature reduces the risk of the dengue infection.
Keywords: Dengue; Reproduction Number; Mathematical Model